STUDENTS’ ABILITY IN WRITING AN ANALYTICAL EXPOSITION TEXT AT ENGLISH DEPARTMENT OF UNIVERSITAS NEGERI PADANG - Annisa Fitri Irwan; An Fauzia Rozani Syafei; Leni Marlina (Universitas Negeri Padang, 2018)
Analytical exposition text is one of genre text that is learned by english department students of Universitas Negeri Padang. The students must be able to write this genre text. The aim of this study is to analyze the ability of students in writing an analytical exposition text. It was a descriptive quantitative research conducted for third semester English departments students of Universitas Negeri Padang. This research focused on how is the students’ ability in writing the thesis statement, argumentation, organization and writing, and the use of evidence of analytical exposition text. The population of this research is third semester English department of Unicersitas Negeri Padang, and the sample was from educational class, it was K-3 class which consists of 20 students. the students were asked to write analytical exposition text and then students’ writing were analyzed by using the rubric of analytical exposition text which consists of four aspect, that are thesis statement, argumentation, organization and writing, and the use of evidence. Based on the findings, there are four students who are in excellent level, five students in proficient level, ten students in fair level, and one student in inadequate level. Overall, the ability of third semester English department students of Universitas Negeri Padang is in proficient level.